Cross-sectional study assessing the performance of the Arabic translated childhood asthma control test. (December 2018) - AlTeneiji, Majid; AlKalbani, Alia; Nasser, Huda; Iram, Durdana; Alblooshi, Afaf; Narchi, Hassib
Abstract The standard Arabic version of the Childhood Asthma Control Test (C-ACT) has never been previously evaluated in Arab countries. We studied its correlation in Arabic speaking children in the United Arab Emirates (UAE), with both the GINA assessment of asthma control and the resulting changes in asthma management. The Arabic C-ACT was completed by the children or by their parents when needed. A GINA based level of asthma control score was assigned by their managing physician. The correlation between the different cut- scores of the C-ACT and GINA were studied. A total of 105 eligible children with asthma (aged between 4 and 11.8 years, 61% boys) were enrolled. The Arabic translated C-ACT had a high reliability (Cronbach alpha 81%) and validity (as it correlated well with the GINA level of control). We found that using it with the traditional cut-score of 19 overestimated the degree of asthma control. Instead, a calculated optimal cut-score of 20 estimated more accurately the level of asthma control as assessed both by the GINA assessment and also by changes in asthma management. The current Arabic version of the C-ACT has a good reliability and validity. By using a single optimal cut-point of 20, it can be used to assess both the level of asthma control and of treatment control. It does not, however, accurately define asthma control when using the originally proposed cut-score of 19. Physicians need to recognise that the C-ACT cut-points may vary in different populations. We suggest that cut-scores of translated versions need to be modified in different geographical settings. Asthma: Improving test accuracy for different populations The cut-off score suggestive of poor disease management in the Childhood Asthma Control Test (C-ACT) may need to be changed for different geographical populations. Majid AlTeneiji at Tawam Hospital in Al-Ain, and co-workers across the United Arab Emirates compared the performance of the Arabic version of the C-ACT with the global asthma control test, GINA, in verifying levels of asthma and treatment control. The researchers enrolled 105 children aged 4 to 11 who completed both tests. The Arabic C-ACT performed with high reliability and validity, but the team found that the original English cut-point score of 19, indicating poor disease management, should be raised to 20 in their Arabic population to improve test accuracy. AlTeneiji's team suggest that the C-ACT test points system may need to be revised for different geographical settings around the world.